Pendampingan Guru dalam Pemanfaatan Media Aplikasi Wordwall untuk Meningkatkan Kemampuan Kognitif Siswa di TK Khairani - Putri Dini Meutia; Erizal Kurniawan; Siti Safura; Luisa Hidayah; Aulia Rahmah (Rengganis Jurnal Pengabdian Masyarakat, 2026)
TK Khairnai, located in Lubok Batee Village, Subdistrict of Ingin Jaya, Aceh Besar, has been established since 2006 and has Akreditasi B. The school has 17 teachers and 3 staff members, and is equipped with 6 classrooms. The main challenges the teachers face include limited use of digital technology in the learning process and students’ difficulty maintaining concentration during the lessons. At the PAUD/TK (early childhood education and kindergarten) level, the use of interactive digital media is essential because it can help improve students’ focus, motivation, and active participation in learning activities. One of the technology-based learning innovations that can be utilized is Wordwall, an interactive learning media that provides various educational games and engaging activities to support the learning process in the classroom. This community service aims to enhance the teachers’ competence in utilising technology at TK Khairani and to improve teacher quality and professionalism. It is carried out through a series of mentoring stages, including: socialisation, training, technology implementation, mentoring, evaluation, and sustainability program. The outcome of this activity is that teachers can integrate the Wordwall effectively into the classroom, and the technological competence of TK Khairani’s is improved